The origin of cycle life degradation of a lead-acid battery under constant voltage charging - Arif Hariyadi; Awan Nugroho; Suwarno Suwarno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Due to its low cost and recycle-ability, the lead-acid battery is widely used in mobile and stationary applications. Despite much research on lead-acid batteries, the effect of charging voltage on the degradation mechanism requires further investigation. In particular, the origin of cycle life degradation remains unclear. In the present work, by using electrochemical tests and materials characterization, we studied the effect of charging voltage at voltages slightly higher than the open-circuit potential (OCP) i.e., 103-107% OCP, on the battery life cycle. The highest degradation was observed at 105% OCP charging voltage. Based on the materials characterization results, we found that the degradation of a lead-acid battery is influenced by the amount of hard sulfate and the sulfate particles' size.